2022
DOI: 10.3389/fphys.2022.912740
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of facemask use on cognitive function during a maximal running aerobic fitness test

Abstract: Background: The aim of the present randomized, crossover study was to determine the physiological and cognitive function responses while wearing a facemask during a maximal running aerobic fitness test.Methods: Fourteen healthy, nonsmoking physical education students (age = 17.5 years, height = 1.72 m, body mass = 70.4 kg) volunteered to participate in this study. They carried out a 20 m multistage fitness test (MSFT) while wearing or not a cloth facemask on two separate occasions performed in random order. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We also examined the effect of wearing a face mask in running speed. A previous study showed that wearing a mask decreased running speed and exercise volume during maximal‐intensity aerobic endurance testing (Slimani et al., 2022). We expected that wearing a mask would cause dyspnea and as a result, less exercise volume, but the data shows the running speed increased (Figure 4a,b).…”
Section: Discussionmentioning
confidence: 97%
“…We also examined the effect of wearing a face mask in running speed. A previous study showed that wearing a mask decreased running speed and exercise volume during maximal‐intensity aerobic endurance testing (Slimani et al., 2022). We expected that wearing a mask would cause dyspnea and as a result, less exercise volume, but the data shows the running speed increased (Figure 4a,b).…”
Section: Discussionmentioning
confidence: 97%